Prophylactic Tranexamic Acid Prevents Postpartum Hemorrhage and Transfusions in Cesarean Deliveries: A Systematic Review and Meta-analysis - Lee, Amy; Wang, Mary Ying-Fang; Roy, Debosree; Wang, Jenny; Gokhale, Abha; Miranda-Cacdac, Lauren; Kuntz, Moriah; Grover, Bryan; Gray, Kendra; Curley, Kathleen L. (American Journal of Perinatology, 2023)
Postpartum hemorrhage (PPH) is the leading cause of maternal mortality worldwide and PPH resulting in transfusion is the most common maternal morbidity in the United States. Literature demonstrates that tranexamic acid (TXA) can reduce blood loss in cesarean deliveries; however, there is little consensus on the impact on major morbidities like PPH and transfusions. We conducted a systematic review/meta-analysis of randomized controlled trials (RCTs) to evaluate if administration of prophylactic intravenous (IV) TXA prevents PPH and/or transfusions following low-risk cesarean delivery. PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) guidelines were followed. Five databases were searched: Cochrane, EBSCO, Ovid, PubMed, and ClinicalKey. RCTs published in English between January 2000 and December 2021 were included. Studies compared PPH and transfusions in cesarean deliveries between prophylactic IV TXA and control (placebo or no placebo). The primary outcome was PPH, and the secondary outcome was transfusions. Random effects models were used to calculate effect size (ES) of exposure in Mantel–Haenszel risk ratios (RR). All analysis was done at a confidence level (CI) of α = 0.5. Modeling showed that TXA led to significantly less risk of PPH than control (RR: 0.43; 95% CI: 0.28–0.67). The effect on transfusion was comparable (RR: 0.39; 95% CI: 0.21–0.73). Heterogeneity was minimal (I2 = 0%). Due to the large sample sizes needed, many RCTs are not powered to interpret TXA's effect on PPH and transfusions. Pooling these studies in a meta-analysis allows for more power and analysis but is limited by the heterogeneity of studies. Our results minimize heterogeneity while demonstrating that prophylactic TXA can lower PPH occurrence and reduce the need for blood transfusion. We suggest considering prophylactic IV TXA as the standard of care in low-risk cesarean deliveries.Key Points
Keywords: tranexamic acid; TXA; postpartum hemorrhage; cesarean; transfusion; prophylactic